Global architecture of F-actin cytoskeleton regulates cell shape-dependent endothelial mechanotransduction - Shao, Yue (2014)
Uniaxial stretch is an important biophysical regulator of cell morphology (or shape) and functions of vascular endothelial cells (ECs). However, it is unclear whether and how cell shape can independently regulate EC mechanotransductive properties under uniaxial stretch. Herein, utilizing a novel uniaxial cell-stretching device integrated with micropost force sensors, we reported the first experimental evidence showing cell shape-dependent EC mechanotransduction via cytoskeleton (CSK) contractile forces in response to uniaxial stretch. Combining experiments and theoretical modeling from first principles, we showed that it was the global architecture of the F-actin CSK that instructed the cell shape-dependent EC mechanotransductive process. Furthermore, a cell shape-dependent nature was relayed in EC mechanotransduction via dynamic focal adhesion (FA) assembly. Our results suggested a novel mechanotransductive process in ECs wherein the global architecture of the F-actin CSK, governed by cell shape, controls mechanotransduction via CSK contractile forces and force-dependent FA assembly under uniaxial stretch.